The Effects of Computer Assisted Auditing Techniques and Auditing Tools (Caatts) on Auditing Activities: Array - Wadesango, Newman; Nyakurera, N. (Acta Universitatis Danubius. Œconomica, 2020)
This research investigated the effects of computer assisted auditing techniques and auditing tools on the auditing activities. The researchers adopted a quantitative research methodology and the sample size consisted of 20 respondents in which the results from the survey were analyzed and presented using the SPSS version 12, graphs, tables and pie charts. The study revealed that CAATTs are used to automate audit tasks, and allows the auditor to analyze accounting data electronically when it is not quite possible to do so manually. Companies are investing in advanced technologies and auditors have to also invest in skills and in advanced capabilities for them to continue offering robust auditing services and to remain efficient and effective in the business environment since these advanced technologies are impacting how to audit. The study also reviewed adoption of advanced technology such as the artificial intelligence, block chain and cloud computing is still fairly low in Zimbabwe but in some few years to come most organizations will harness these powerful and robust technologies and auditors must be prepared to upgrade themselves and embrace these technologies.